REGIONAL ASPECTS OF CANADIAN SUPPLY MANAGEMENT SYSTEM IN THE AGRICULTURAL BUSINESS AND ITS APPLICATION IN UKRAINE - Igor Smyrnov (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
Revealed the features and achievements of Canadian agrilogistics and supply management, which is an important factor of the high efficiency of agriculture in Canada, which is known worldwide as one of the largest manufacturers and exporters of various agricultural products. Shown the mechanism of functioning farm tariff quotas with the possibility of sharing in the domestic market, which is now successfully proven in industrial poultry and dairy industry of Canada. Given recommendations for the application of Canadian supply management for Ukraine agriculture.